Nerolidol nanospheres increases its trypanocidal efficacy against Trypanosoma evansi: New approach against diminazene aceturate resistance and toxicity - Baldissera M.D. (2016)
© 2016 Elsevier Inc..The aims of this study were to develop nerolidol-loaded nanospheres, and to evaluate their efficacy in vitro and in vivo against Trypanosoma evansi, as well as to determine their physicochemical properties, morphology, and any possible side effect in vitro against peripheral blood mononuclear cell (PBMC). The nanospheres showed an adequate particle size (149.5 nm), narrow particle distribution (0.117), negative zeta potential (-12.8 mV), and pH of 6.84, such as observed by transmission electron microscopy. In vitro, a trypanocidal effect of nerolidol and nanospheres containing nerolidol was observed at 0.5, 1.0, and 2.0%, i.e., both treatments showed a faster trypanocidal effect compared to chemotherapy (diminazene aceturate - D.A.). T. evansi infected mice were used to evaluate the effects of nerolidol-loaded nanospheres regarding pre-patent period, longevity, and therapeutic efficacy. Oral administration of nerolidol-loaded nanospheres at 1.0 mL/kg/day during 10 days increased mice survival (66.66%) compared to 0% and 33.33% of mice survival when treated with nerolidol in its free form and D.A., respectively. Cytotoxic study indicated that both treatments showed no side effects in vitro against PBMC, an important marker used in toxicological surveys. Therefore, nanoencapsulation increased the therapeutic efficacy of nerolidol against T. evansi, and can be used as an alternative treatment for T. evansi infection.